Pengadaan bahan pustaka di Perpustakaan Rekso Pustoko Mangkunegaran - Nunung Aliyati Fajer (Asosiasi Perpustakaan Perguruan Tinggi Islam Wilayah Jawa Timur (APPTIS Jatim), 2022)
This article focuses on research on the procurement of library materials at Rekso Pustoko Library Mangkunegaran. This study aims to describe: (1) general procedires; (2) method; (3) types of library material procerement in Rekso Pustoko Library; (4) constraints in the procurement of library materials. The activity of collecting research materials was carried out by means of observation, literature study, archive study and interview. Them analyze the overall collecting research obtained carefully and descriptive to obtain the following points. The result showed that the procurement of library materials at Rekso Pustoko Library Mangkunegaran mostly came frm donations / gift / donations from student, lecturers, cultural activist and internal internal staff. Includes: book, clipping, theses, scientifc journal, and others.